Elevated lymphocyte count at time of acute myeloid leukemia diagnosis is associated with shorter remission. Issue 11 (2nd November 2015) - Bar, Merav; Othus, Megan; Park, Hanahlyn M.; Sandhu, Vicky; Chen, Xueyan; Wood, Brent L.; Estey, Elihu
Abstract : In solid tumors, decreased absolute lymphocyte count (ALC) at diagnosis was found to be associated with poorer outcome, but there is only limited data on the impact of ALC in acute myeloid leukemia (AML). In this study we evaluated the prognostic value of ALC on outcome in 259 adult patients with AML who responded to induction therapy. Higher than normal ALC at diagnosis was associated with shorter remission (HR 4.06; p < 0.001), and decreased relapse free and overall survival (HR 3.47; p < 0.001 and HR 3.85; p < 0.001 respectively). Flow cytometry showed low frequency of natural killer (NK) cells and high frequency of CD4+ T cells (which includes the subset of T regulatory cells) in the high ALC group. Low frequency of NK cells and potentially high frequency of inhibitory T regulatory cells may result in weaker immune responses against residual leukemia and may explain the poorer outcome of the high ALC group.